SQ3R: Cara Efektif Merebut Atensi Siswa pada Pembelajaran Keterampilan Membaca Pemahaman - Kultsum, Ummu; Salim, Herli (Universitas Pendidikan Indonesia Kampus Serang, 2022)
Ideally grade 4 elementary school students should have understood the contents of the reading well, but in reality, there are still difficulties in understanding the main points of a text. This is marked when students have enabled to determine the main idea of a particular paragraph because of a lack of attention in learning. If this problem is not followed up, the learning objectives can be difficult to achieve. By conducting this research, the researcher wants to know whether reading by applying the SQ3R method can work effectively so that the level of student understanding will increase. Researchers used a qualitative approach in their research, then Classroom Action Research (CAR) with Kemmis and McTaggart models as research methods. The place that has been determined by the researcher is SDN Karodangan which is located in Taktakan, Serang. The main points discussed by the researcher were students who were in grade 4 which consisted of 9 students. The action that has been carried out has proven an increase in students' reading comprehension skills. Before the action, the average value of students' reading comprehension skills was 43.3 and 22.2% as a percentage. When the first action, the average value of students' reading comprehension skills obtained was 60 and 44.4% as a percentage. Then the second action, the average value of students' reading comprehension skills increased to 85.5 and 88.8% as a percentage. Based on the description of thedata, it concluded that the SQ3R method has proven to be effective in capturing students' attention so that their understanding can increase.